Hodnocení finanční situace podniku a návrhy na její zlepšení - Kinclová, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalářská práce hodnotí finanční situaci podniku DIAMO, s. p. v období 2003 - 2007, prostřednictvím vybraných ukazatelů finanční analýzy. Na základě zjištěných údajů jsou navržena doporučení, která by měla vést ke zlepšení finančního stavu podniku.

This bachelor's thesis evaluates the financial situation of DIAMO, s. p. in the period 2003 - 2007, through selected indicators of financial analysis. On the basis of received data, recommendations which should lead for improving the financial status of the company, are suggested.
Evaluation of the Company's Financial Situation and Improvement Proposals
Keywords: Finanční analýza; horizontální analýza; vertikální analýza; poměrová analýza; výkaz zisku a ztrát; návrhy na zlepšení finanční situace.; Financial analysis; horizontal analysis; vertical analysis; proportional analysis; profit and loss statement; proposals for improving the financial situation.